2020
DOI: 10.1039/d0se00372g
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of salinity gradient energy recovery by reverse electrodialysis in a seawater reverse osmosis desalination plant

Abstract: LCA of lab-scale and large-scale stand-alone RED stacks and an up-scaled RED system co-located with a SWRO desalination plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…However, a detailed cost-efficiency analysis would be needed to establish the eco-efficiency of this strategy, especially when considering thermal energy requirements. Tristán et al [ 302 ] carried out such evaluation for a SWRO-RED process. Their detailed LCA study demonstrated the low environmental impact of RED (comparable to solar and wind power systems) and identified that the fabrication of PES membrane spacers is the step with the highest energy cost.…”
Section: Integration Of Ed Technologies In New Sustainable Strategmentioning
confidence: 99%
“…However, a detailed cost-efficiency analysis would be needed to establish the eco-efficiency of this strategy, especially when considering thermal energy requirements. Tristán et al [ 302 ] carried out such evaluation for a SWRO-RED process. Their detailed LCA study demonstrated the low environmental impact of RED (comparable to solar and wind power systems) and identified that the fabrication of PES membrane spacers is the step with the highest energy cost.…”
Section: Integration Of Ed Technologies In New Sustainable Strategmentioning
confidence: 99%
“…where GWP 100, RED stack is the GWP of the RED stack (kg CO2-eq) as defined in Tristán et al's LCA [66], and E plant and LT are the retrieved exergy yield or net energy yield (kWh year −1 ) and the lifetime (20 years) of the RED plant, respectively. The annual energy yield of a RED plant working at full capacity-i.e., 8760 full load hours per year (FLH)-is given by: Figure A1.…”
Section: Discussionmentioning
confidence: 99%
“…The local grid mix's GWP 100 indicator per unit of electricity produced was retrieved from the ecoinvent database 3.6 [65] (dataset: market for electricity, medium voltage, Appendix B). The GWP 100 of the industrial-scale RED stack was estimated based on the Tristán et al [66] life cycle assessment (LCA) of a RED unit equal to that of our assessment, normalized to the energy yield (net specific energy or specific salinity gradient exergy retrieved for conversion) over the lifetime of the RED plant (20 years) in each location and energy supply scenario (Appendix B).…”
Section: Estimation Of Ghg Emissions: Global Warming Potential (Gwp)mentioning
confidence: 99%
“…In this sense, the integration of RED into desalination facilities is presented as a promising alternative towards the achievement of self-sufficient or low-energy consuming systems, although capital costs are still limiting its installation. Moreover, life cycle assessments of RED units conclude that RED is environmentally competitive with other RE such as solar PV energy or wind energy [67].…”
Section: Alternative A2-salinity Gradient Energy Harvestingmentioning
confidence: 99%